Bacterial Cellulose-BasedBiodegradable Plasticfrom Pineapple (Ananassativus) Skin Waste: The Effectof Sorbitol On The QualityOf The Biodegradableplastic - Putra, Ananda (Journal of Chemical Natural Resources, 2019)
The aim of this research was to investigate the effect of sorbitol on the quality ofbacterial cellulose-based biodegradable plastic from pineapple skin waste. Various concentrations of sorbitol as the plasticizer were added into a fermentation medium in the synthesis of bacterial cellulose-sorbitolcomposite (BCSC). The BCSCobtainedwas purified by soaking it into a cycled water-NaOH-water. The purified BCSC wasthen compressed using a hot press with the pressure of 300 psi to obtain BCS plastic. The BCS plasticwas characterized in the aspect of physical properties (water content,the degree of swelling), mechanical properties (tensile strength,elongation, elasticity), molecular structure (functional groups, thedegree of crystallinity), and biodegradability. The results showed that the percentage ofwater content anddegree of swelling of theBCS plastic increased with the addition of sorbitol concentrations. The maximum tensile strength was obtained with the addition of 10.5% sorbitol (%v/v). The degrability of the BCS plastic was up to 59% until the 9th day. TheFTIR results showed that functional groups appeared in the BCS plastic were similar to those of the BC. The degree of crystallinity of the BCSplastic decreased with the increasing concentration of sorbitol.